2021
DOI: 10.1111/apm.13195
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of the tumor immune microenvironment and immune checkpoint pathway in primary central nervous system diffuse large B‐cell lymphoma in the North Indian population

Abstract: Prognostic implications of the tumor immune microenvironment and immune checkpoint pathway in primary central nervous system diffuse large B-cell lymphoma in the North Indian population. APMIS. 2022; 130: 82-94. Primary central nervous system-diffuse large B-cell lymphoma (PCNS-DLBCL) is a rare, extranodal malignant lymphoma carrying poor prognosis. The prognostic impact of tumor microenvironment (TME) composition and the PD-1/ PD-L1 immune checkpoint pathway are still undetermined in PCNS-DLBCL. We aimed to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Majority of the cases were already worked-up for Han’s algorithm as a part of two earlier published studies. [ 8 , 9 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the cases were already worked-up for Han’s algorithm as a part of two earlier published studies. [ 8 , 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…Like the previous study, the standard universal cutoffs for positivity were considered. [8,9] e IHC slides were independently evaluated by two pathologists, who were blinded to the clinical data. e cutoff for MYC, BCL6, and BCL2 positivity were taken as 40%, 50%, and 50%, respectively.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Some researchers showed that a high density of M2 TAMs was correlated with shortened survival in DLBCL (1,3,17,23). However, several other studies did not demonstrate such association (20,24,25,27,(29)(30)(31)(32). Therefore, we performed this meta-analysis to explore the role of TAMs in DLBCL progression and the prognostic value of TAMs in DLBCL patients.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies showed that a high density of CD68 + TAMs was associated with favorable prognosis (3,20,21). A few other studies failed to demonstrate such association (4,18,(22)(23)(24)(25)(26)(27). By contrast, Cai et al (28) and Carreras et al (17) showed that high density of CD68 + TAMs correlated with inferior outcome.…”
Section: Introductionmentioning
confidence: 99%
“…There are many target receptors in PCNSL apart from B-cell antigen receptor and Toll-like receptor signaling, such as programmed cell death-1 (PD-1)/PD-1 Ligand and immune activation shown by presence of tumor infiltrating lymphocytes. So, targeting one pathway may not be sufficient to treat such a debilitating disease[ 15 , 16 ]. CSF analysis may not provide information about the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%